The role of participation in community theatre for development interventions: a case study of the Wadzanayi Farm Project in Lalapanzi, Zimbabwe - Yule, Julia (My University, 2012)
Participation has now become an established orthodoxy in theatre and development thinking and practice. But what exactly is it and how best it should be pursued in community development remains the question. This study examined the role of participation in community theatre for development interventions in Zimbabwe drawing from the Wadzanayi community as a case study. A number of paradigms of participation were explored in the search for a better and more effective model that prioritises the community. Among these paradigms, transformative participation proved to be more people centred as compared to other paradigms where participation was goal centred and donor driven. The study acknowledged that even though practitioners are striving to achieve transformative development they constantly fall in the trap of holding back power and control from the local people who are the primary stakeholders. The research also examined the monitoring and evaluation process and how participation was framed in and through live performance. The research concludes that community participation in theatre for development interventions takes on different forms at different stages of the project cycle, resulting in participation being handled differently at various stages.
M.A. University of the Witwatersrand, Faculty of Humanities (Dramatic Arts), 2012